Technology Research Database of Cambridge Scientific Abstracts (CSA) - Megan Sapp (Issues in Science and Technology Librarianship)
Presents information on the Technology Research Database of Cambridge Scientific Abstracts (CSA). Content of the database; List of CSA search interfaces; Limitation of the database.